2019
DOI: 10.3892/mco.2019.1970
|View full text |Cite
|
Sign up to set email alerts
|

Depression following graft-versus-host disease in a patient with acute lymphoblastic leukaemia: A case report

Abstract: There is increasing evidence to suggest an association between depression and inflammation, with patients suffering from immune mediated-disorders exhibiting higher levels of depression. Inflammation in depression is a potential target for the development of novel treatment strategies. The present study presents a clinical case in which a patient with an underlying inflammatory condition acutely developed a severe depressive episode resulting in a sudden, dramatic change in their clinical picture. This case, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Recent observational studies have identified that chronic GVHD is a risk factor for depression following an HCT due to the release of pro-inflammatory cytokines, which is seen in other medical conditions accompanied by inflammation such as cancer, autoimmune disease and post viral infections ( 23 ). In GVHD, pro-inflammatory cytokines are able to activate central nervous system circuits leading to neurobehavioral and affective responses such as depressive mood, fatigue, sleep disturbance, anorexia and decrease in cognition, seen in other chronic inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent observational studies have identified that chronic GVHD is a risk factor for depression following an HCT due to the release of pro-inflammatory cytokines, which is seen in other medical conditions accompanied by inflammation such as cancer, autoimmune disease and post viral infections ( 23 ). In GVHD, pro-inflammatory cytokines are able to activate central nervous system circuits leading to neurobehavioral and affective responses such as depressive mood, fatigue, sleep disturbance, anorexia and decrease in cognition, seen in other chronic inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In GVHD, pro-inflammatory cytokines are able to activate central nervous system circuits leading to neurobehavioral and affective responses such as depressive mood, fatigue, sleep disturbance, anorexia and decrease in cognition, seen in other chronic inflammatory disorders. It is believed that anti-depressant medications have a role in suppressing immune mediated disorders in addition to providing treatment for depression ( 23 ). Furthermore, research also suggests that anti-inflammatory drugs can improve depressive symptoms in patients with chronic inflammatory diseases independent of improvement in the physical illness ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation